An analysis of business and financial performance of PT Industri Jamu dan Farmasi Sido Muncul Tbk in 2019-2021 - Aisy, Afifah Rohadatul; Bachtiar, Arief (Proceeding International Conference on Accounting and Finance, 2024)
This study aimed to determine the business conditions and financial performance of the Pharmaceutical Industry and Jamu Industry in Indonesia which were listed on the IDX, especially PT Industri Jamu dan Farmasi Sido Muncul Tbk (Sido Muncul) during the period 2019 to 2021. The data used in this research was obtained from various sources, including the complete annual reports of pharmaceutical companies listed on the IDX for the 2019-2021 period. Financial data obtained from www.idx.co.id and the company's official website. The Palepu model (2004) was used to analyze the business and financial performance of the Pharmaceutical Industry, Jamu Industry, and PT Sido Muncul during the period 2019 to 2021. The results of this study showed that there was high competition between companies (rivalry among existing firms), both within the Pharmaceutical Industry and Jamu Industry in Indonesia. This can be seen from data from the Ministry of Health in 2021 that the number of pharmaceutical and jamu industries has increased from year to year. In addition, the high percentage of profits made the pharmaceutical and jamu industry very attractive to illegal producers. PT Sido Muncul was able to face business competition with a qualified differentiation strategy as a corporate strategy. All company progress was explained in detail in the annual financial reports, especially in the notes to the financial statements and there were no red-flags or significant differences or deviations. Based on the ratio analysis, it showed that the Pharmaceutical and Sido Muncul Industries were in a liquid and solvable state, and the effectiveness and productivity of the Pharmaceutical and Sido Muncul Industries in managing company assets increased so that the profit earned also increased. In addition, Sido Muncul's high Return on Investment value indicated the company's ability to create returns on investment that were used for very effective operations. Sido Muncul was in a healthy condition and was not bankrupt as seen from the results of calculations using the Altman Z-Score method.